A practical guide to the Charter: section 11(b) - Gold, Alan D. (LexisNexis Canada, 2019)
"This is a reference tool for criminal law practitioners on section 11(b) of the Canadian Charter of Rights and Freedoms, which guarantees the right to a trial within a reasonable period of time. It discusses key cases and topics of interest."-- Provided by publisher.